The impact of multisensory learning model-based tale-telling on listening skills and student opinions about it - Gazioğlu, Mustafa; Karakuş, Neslihan (Frontiers in Education, 2023)
This study aims to reveal the impact of multisensory learning model-based tale-telling on listening skills. The research was carried out under a hybrid research design using both quantitative and qualitative research methods together. The study group of the research consists of 13 fifth-grade students in total who were studying in a public school during the 2020 to 2021 academic year. Students were involved in the research voluntarily and with parental permission. The following data collection tools were used in the research: “Attitude Scale Towards Improving Listening Skills with Tales,” which was created by the researcher, tale diaries, and tale self-evaluation forms. Quantitative and qualitative data analysis methods were used to analyze the research data. T-test analysis was applied to the quantitative data after transferring them to the SPSS data analysis program; on the other hand, content analysis was used to analyze the qualitative data. As a result of the research, it was concluded that the multisensory learning method-based tale-telling has a positive impact on the attitudes of the fifth-grade students towards tale listening. In light of the results, it was concluded that parents were satisfied with the activities for multisensory tale-telling, students have understood the plots of the tales correctly, themes were remembered correctly by the students most of the time, and parents have shown a positive attitude towards tale listening.